Fenomenismo no Quarto Paralogismo da Crítica da Razão Pura de I. Kant: a leitura berkeleyana do idealismo transcendental - Garcia, Ernane São João (Universidade Federal de São Carlos, 2022)
The philosophies of Kant and Berkeley aim to refute skepticism and, for this purpose, they defend the thesis according to which the objects of our knowledge are, respectively, “representations” or “ideas”. In general, this thesis is classified in the literature as “phenomenism”. Such similarity between the position of both philosophers has led many critics to see the position of Immanuel Kant in the Fourth Paralogism of the first edition of the Critique of Pure Reason (1781), a passage in which the philosopher intends to refute the “empirical idealism”, as being identical to that of the philosopher George Berkeley in the Principles (1710) and the Dialogues (1713). This reading, defended, among others, by Norman Kemp Smith, Colin M. Turbayne and James Van Cleve, conflicts with two assertions by Kant: that his transcendental idealism is “the opposite” of Berkeley's and that the Fourth Paralogism differs from the Refutation of Idealism of the second edition of the first Critique only in the way of proving. Against this Berkeleyan reading of the Fourth Paralogism, we argue that Kant's position in this passage is fundamentally different from Berkeley's. To prove our thesis, we try to determine the nature of Berkeleyan phenomenism, which was determined as an ontological phenomenism, and then to verify if Kantian phenomenism is identical to that. This was possible by the application of the distinction, presented by Kant in the Fourth Paralogism, according to which objects can be considered in two senses, the empirical and the transcendental, to the Kantian notion of “representation”, which allowed us to determine whether the Kantian concept of “representation” is or is not equivalent to the Berkeleyan concept of “idea”. As a result, we show that the Kantian conception of “representation” is radically new in the light of the philosophical tradition and that Kant's phenomenalism is an epistemic phenomenalism, being, therefore, radically different from Berkeley's ontological phenomenalism, which allows us to resolve the two problems outlined.
Phenomenalism in the Fourth Paralogism of I. Kant's Critique of Pure Reason: the Berkeleyan reading of transcendental idealism
Keywords: Idealismo transcendental; Idealismo empírico; Fenomenismo; Realismo transcendental; Realismo empírico; CIENCIAS HUMANAS::FILOSOFIA::EPISTEMOLOGIA; CIENCIAS HUMANAS::FILOSOFIA::HISTORIA DA FILOSOFIA